MODEL-DRIVEN SOFTWARE ENGINEERING FOR SCALABLE ENTERPRISE APPLICATIONS (Eureka Journal of Computing Science & Digital Innovation, 2025)
The rapid expansion of enterprise systems, driven by digital transformation initiatives, has increased the need for scalable, maintainable, and adaptable software architectures. Model-Driven Software Engineering (MDSE) has emerged as a systematic approach to managing software complexity through formal modeling, automated code generation, and repeatable development workflows. This paper investigates the role of MDSE in building scalable enterprise applications, analyzing its benefits, challenges, and implementation potential in modern cloud-native and distributed environments. Using qualitative case analysis and a structured evaluation model, the study demonstrates that MDSE increases development productivity by 32%, reduces architectural inconsistencies by 41%, and enhances system scalability through abstraction-driven design. The paper concludes with a recommended MDSE adoption framework for enterprise organizations.
Keywords: MDSE, enterprise applications, scalability, UML, model transformation, cloud-native systems, code generation, digital innovation.